ENFOQUE SEMÁNTICO-COGNITIVO DEL ESTUDIO DE UNA PERSONA DE LENGUAJE EN EL SISTEMA DE VALORES HUMANOS E INDIVIDUALES - Fisenko , Olga; Vlada, Nikitina; Bodrova , Tatyana (Revista Inclusiones, 2018)
In the article, the linguistic personality is considered as a complex phenomenon that exists on the border of language, consciousness and culture. It is proved that the semantic-cognitive approach is the most productive in the study of the linguistic personality, which allows considering the linguistic personality as a carrier, keeper and translator of both universal and individual values. Individual values fit into the general categorical system of universal human values, but unlike them are less stable; they can change during the life of a person.